Evaluating plyometric exercises using time to stabilization - Ebben, W. P.; van der Zanden, T.; Wurm, B. J.; Petushek, E. J. (The Journal of Strength and Conditioning Research, 2010)
Plyometric exercises are frequently used in strength and conditioning and rehabilitation programs because the landing phase of these exercises requires dynamic stabilization. This study examined the differences in landing stability of a variety of plyometric exercises by assessing time to stabilization (TTS), its reliability, and sex differences therein. Forty-nine men and women performed a variety of plyometric exercises thought to represent a continuum of difficulty of dynamic stabilization during landing. Plyometric exercises included line hops, cone hops, squat jumps, tuck jumps, countermovement jumps, dumbbell countermovement jumps, and single leg countermovement jumps, each performed for 3 repetitions on a force platform. A 2-way mixed analysis of covariance with repeated measures for plyometric exercise type was used to evaluate the main effects for plyometric exercise type and the interaction between plyometric exercise type and sex for TTS. Subject jumping ability was evaluated as a covariate. Results revealed significant main effects for plyometric exercise type (p = 0.001) and for the interaction between plyometric exercise type and sex (p = 0.002). Bonferroni adjusted post hoc analysis demonstrated differences in TTS between a number of plyometric exercises for men and women. Reliability analysis revealed intraclass correlation coefficients ranging from 0.51 to 0.86 with no significant difference between trials (p > 0.05). Practitioners who use plyometrics to train dynamic stability should create programs that progress the intensity of the exercises based on the results of this study. This study also demonstrated that TTS is moderately to highly reliable for a variety of jumping conditions for both men and women.